Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

-4K+2(5k-6)=-3k-39
How do i solve it to get my answer.


Sagot :

First we have to multiply 2 times 5k and -6 and simplify
-4k+2(5k-6)=-3k-39
-4k+10k-12=-3k-39
-4k+10k-12=-3k-39
6k-12=-3k-39           /+3k
9k-12=-39               /+12
9k=27                    /:9
k=27:9
k=3 - its the answer